2013
DOI: 10.1002/stc.1556
|View full text |Cite
|
Sign up to set email alerts
|

Optimum design for more effective tuned mass damper system and its application to base-isolated buildings

Abstract: Base-isolated structures are vulnerable to long-period ground motions due to resonances. The hybrid control strategy combining traditional tuned mass dampers (TMDs) with base-isolation systems has been proved by some researchers to be effective in preventing the resonant behaviors. However, large space for TMDs is required because of large stroke lengths of TMDs, which may be difficult to realize in practical applications. In this paper, a non-traditional TMD that is directly connected to the ground by a dashp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 22 publications
(27 reference statements)
1
76
0
Order By: Relevance
“…In the context of hybrid control strategies, applications of BIS in conjunction with a TMD attached immediately above or below the isolation oor of the building have been extensively discussed in the literature [17][18][19][20]. It has been found that by attaching a TMD to the BIS, a certain reduction of the displacement demand of a base-isolated structure is achieved, depending on the TMD mass.…”
Section: Base Isolation With Supplemental Rotationalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of hybrid control strategies, applications of BIS in conjunction with a TMD attached immediately above or below the isolation oor of the building have been extensively discussed in the literature [17][18][19][20]. It has been found that by attaching a TMD to the BIS, a certain reduction of the displacement demand of a base-isolated structure is achieved, depending on the TMD mass.…”
Section: Base Isolation With Supplemental Rotationalmentioning
confidence: 99%
“…e optimization procedure here proposed resembles tuning procedures for TMD-based control strategies [10,20,27,44], wherein some parameters are the free design variables sought in the optimization problem, while other parameters are supposed known. e TMDI is characterized by four parameters in the most general case, namely, μ t , β t , ω t , and ζ t .…”
Section: Optimal Design Of the Tmdi And Tuningmentioning
confidence: 99%
“…Nevertheless, large mass ratio TMDs have been explored mainly for earthquake inputs (Chowdhury et al, 1987;Feng and Mita, 1995;Arfiadi, 2000;Villaverde, 2000;Zhang and Iwan, 2002;Mukai et al, 2005;Villaverde et al, 2005;Tiang et al, 2008;Matta and De Stefano, 2009;Petti et al, 2010;Angelis et al, 2012;Nishii et al, 2013;Xiang and Nishitani, 2014). It should be pointed out that several projects are being planned in Japan aiming at installation of large mass pendulum systems at roof and usage of upper stories as TMD masses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, large mass ratio TMDs were tackled for base-isolated buildings (Villaverde, 2000;Villaverde et al, 2005;Angelis et al, 2012;Nishii et al, 2013;Xiang and Nishitani, 2014). While usual tall buildings exhibit large displacement near the top story because of contribution of almost uniform inter-story drifts, base-isolated buildings show relatively large displacement at the base-isolation story near ground surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation